2017
DOI: 10.4236/jbnb.2017.82009
|View full text |Cite
|
Sign up to set email alerts
|

Homogenized Porcine Extracellular Matrix Derived Injectable Tissue Construct with Gold Nanoparticles for Musculoskeletal Tissue Engineering Applications

Abstract: A unique porcine extracellular matrix (ECM) derived injectable tissue construct with 100 nm or 20 nm gold nanoparticles (AuNP) was developed for musculoskeletal tissue engineering applications. ECM has been shown to encourage cellularity and tissue remodeling due to its release of growth factors while AuNP have been shown to reduce reactive oxygen species (ROS) levels. Injectable tissue constructs were created by homogenizing decellularized porcine diaphragm tendon conjugated with 100 nm or 20 nm AuNP at 1x, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The use of metallic nanofillers (e.g., gold or silver nanoparticles) is interesting for biomedical applications to enhance the electrical conductivity or antimicrobial properties of tissues. For example, the incorporation of gold nanoparticles into extracellular matrixes (ECM) demonstrated the enhancement of the cellularity by reinforcing the ECM, while mitigating the inflammation for musculoskeletal tissue engineering applications [24]. Silver, in the form of nanoparticles, is also well recognized for its antimicrobial properties, specifically as an alternative to antibiotic drugs.…”
Section: Nanocomposites With Metallic-based Nanofillersmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of metallic nanofillers (e.g., gold or silver nanoparticles) is interesting for biomedical applications to enhance the electrical conductivity or antimicrobial properties of tissues. For example, the incorporation of gold nanoparticles into extracellular matrixes (ECM) demonstrated the enhancement of the cellularity by reinforcing the ECM, while mitigating the inflammation for musculoskeletal tissue engineering applications [24]. Silver, in the form of nanoparticles, is also well recognized for its antimicrobial properties, specifically as an alternative to antibiotic drugs.…”
Section: Nanocomposites With Metallic-based Nanofillersmentioning
confidence: 99%
“…In addition, conjugation, or cross-linking is generally used to assure covalent grafting between nanoparticles and tissues and thus improving the integration of nanofillers within matrixes. For example, Smith et al conjugated gold nanoparticles with a porcine extracellular matrix by first grafting 2-mercaptoethy-lamine (MEA) on gold nanoparticles before conjugation with 1-ethyl-3-[3-dimethylainopropyl] carbodiimide (EDC) [24].…”
Section: Sol-gel Technologiesmentioning
confidence: 99%
“…[23][24][25] Amine functionalization of NPs is performed by conjugation with an organic compound containing both an amine and thiol functional groups such as glutathione, cysteine, or cysteamine; with compounds containing amine and hydroxyl groups such as ethanolamine; or with other organic coating agents, such as butylamine, ethylenediamine, heptylamine, di-amino-propane, allylamine, or ammonia, which provide NPs with amine groups that can react with carboxyl groups in matrices. [26][27][28][29] Carboxyl functionalization of NPs can also be performed using acids that provide reactive carboxyl groups, such as poly(D, L-lactide-co-glycolide) (PLGA) and thioctic acid. 30,31 Although functionalized NPs can more efficiently bind decellularized matrices, their homogeneous distribution within the matrix is altered; this is because functionalized NPs are more likely to aggregate before loading into the matrices.…”
Section: Mechanisms Of Np Binding To Decellularized Matricesmentioning
confidence: 99%
“…That study revealed that AuNPs (especially 20 nm AuNPs) can enhance fibroblast migration and functionality of the injectable extracellular matrix (ECM) constructs. 28 However, although the gold nanostructures generally improve porcine tendinous diaphragmatic material, their size and shape for optimal biocompatibility have not yet been determined. Application of single-walled carbon nanotubes (SWCNTs; 1.5 nm × 200-300 nm), which have excellent mechanical and conductive properties, was examined by Deeken et al 55 That study aimed to improve resistance to collagenase and tensile strength of the diaphragmatic porcine tendon.…”
Section: Expanding Potential Applications Of Decellularized Tendinousmentioning
confidence: 99%
See 1 more Smart Citation